The Influence of Positive Discipline, Differentiated Instruction Strategies, and Learning Motivation on the Learning Outcomes of Buddhist Religious Education - Chandra, Chandra; Gde Yadnyawati, Ida Ayu; Candra, Alexander (Riviera Publishing, 2024)
This study aims to examine and understand the influence of positive discipline, differentiated instruction strategies, and learning motivation on the learning outcomes of Buddhist Religious Education students at Maitreyawira Private High Schools throughout Indonesia. This research uses a quantitative method. Data collection was conducted by distributing questionnaires consisting of positive discipline variables, differentiated instruction strategies, learning motivation, and learning outcomes using multiple linear regression analysis techniques. The total sample taken was 92 students from Maitreyawira Private High Schools across Indonesia (Palembang, Batam, Deli Serdang, Tanjung Pinang, Jakarta, and Kisaran) out of a total population of 1,089. The results of this study show that by comparing the values of tcount > ttable (2.687 > 1.662), positive discipline has a partial positive and significant effect on the Buddhist education learning outcomes of Maitreyawira High School students; Furthermore, looking at the comparison of tcount > ttable (2.162 > 1.662), the differentiated instruction strategies have a partially positive and significant effect on the Buddhist Education learning outcomes of Maitreyawira High School students; with a comparison of tcount > ttable (7.280 > 1.662), learning motivation has a partially positive and significant effect on the Buddhist Education learning outcomes of Maitreyawira High School students; and the results of the f test where fcount > ftable (64.881 > 2.71) shows that positive discipline, differentiated instruction strategies and learning motivation have a positive and significant effect simultaneously on learning outcomes.